Antibacterial properties of AgNO3-activated carbon composite on Escherichia coli: inhibition action - Yanou Rachel, Nkwaju; Abdelaziz, Baçaoui; Julius Nsami, Ndi; Daouda, Kouotou; Abdelrani, Yaacoubi; Mehdi, Lourrat; Khalid, Lafdi; Joseph, Ketcha Mbadcam (International Journal of Advanced Chemistry, 2018)
AgNO3- activated carbon composite based palm kernel shell was prepared by hydrothermal carbonization. The concentration of AgNO3, activation temperature and impregnation time were investigated on five responses (iodine number, methylene blue number, BET surface area, micropore volume and total pore volume). The most influential parameters of the preparation process were optimized using the Doehlert optimal design. From the ANOVA, the following optimal conditions of preparation were retained: 0.068 mol/L, 210Â°C and 3.7 h for AgNO3 concentration, activation temperature and impregnation time respectively. The activated carbon (AC) and the composite (AC-AgNO3) were characterized using Fourier Transform infrared spectroscopy, X-Ray diffraction, Scanning Electron Microscopy coupled to Energy Dispersive X-ray spectroscopy and measurements of the surface area. The XRD pattern and SEM-EDX clearly confirmed the presence of silver in the composite. The experimental parameters of AC- AgNO3 composite were as followed: 708.44 mg/g; 293.09 mg/g; 713.0 m2/g; 0.49 cm3/g and 0.76 cm3/g, for iodine number, methylene blue number, BET surface area, micropore volume and total pore volume of AC- AgNO3 respectively. The antibacterial test carried on Escherichia Coli showed that AC-AgNO3 composite has a high-improved antibacterial property of 99.99% fixation with a dosage of 1500 ppm for 5 hours of contact time.